Selected Areas in Cryptography 18th International Workshop, SAC 2011, Toronto, ON, Canada, August 11-12, 2011, Revised Selected Papers - Miri, Ali.; Vaudenay, Serge; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 18th Annual International Workshop on Selected Areas in Cryptography, SAC 2011, held in Toronto, Canada in August 2011. The 23 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 92 submissions. The papers are organized in topical sections on cryptanalysis of hash functions, security in clouds, bits and randomness, cryptanalysis of ciphers, cryptanalysis of public-key crypthography, cipher implementation, new designs and mathematical aspects of applied cryptography.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computer vision; Computer Science; Data Encryption; Systems and Data Security; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Information Systems Applications (incl. Internet).; Computer Imaging, Vision, Pattern Recognition and Graphics